2021
DOI: 10.1016/j.ejmech.2020.113059
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic prodrugs: Design of a dual butyrylcholinesterase inhibitor and 5-HT6 receptor antagonist with therapeutic interest in Alzheimer’s disease

Abstract: Beside acetylcholinesterase, butyrylcholinestersase could be considered as a putative target of interest for the symptomatic treatment of Alzheimer's disease (AD). As a result of complexity of AD, no molecule has been approved since 2002. Idalopirdine, a 5-HT6 receptors antagonist, did not show its effectiveness in clinical trial despite its evaluation as adjunct to cholinesterase inhibitors. Pleiotropic molecules, known as multitarget directed ligands (MTDLs) are currently developed to tackle the multifactori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 60 publications
(89 reference statements)
1
21
0
Order By: Relevance
“…The inhibition of BChE has been advocated in the later stage of Alzheimer's disease. During the progression of the disease, the BChE level increases, exacerbating the conditions of the patient [43]. Herein, the ability of N. baytopii aerial parts extracts and essential oil to inhibit α-amylase and α-glucosidase was also evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of BChE has been advocated in the later stage of Alzheimer's disease. During the progression of the disease, the BChE level increases, exacerbating the conditions of the patient [43]. Herein, the ability of N. baytopii aerial parts extracts and essential oil to inhibit α-amylase and α-glucosidase was also evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of BuChE has been advocated in the later stage of Alzheimer’s disease. During the progression of the disease, BuChE level increases, exacerbating the conditions of the patient [ 56 ]. The ability of the extracts to inhibit enzymes targeted in the management of diabetes type II, namely α-amylase and α-glucosidase, was presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Many Alzheimer disease drugs were being suggested but the major drawback is that all the drug targets one pathway (Oliveri, 2015) (Toublet et al, 2020) but ROS responsive prodrug is a multi-targeted directed ligand which shows anti-inflammatory activity and also inhibits the acetylcholinesterase enzyme. The ROS responsive prodrug therapy is the most advanced treatment for neurodegenerative disorder (Oliveri, 2015).…”
Section: Ros Responsive Prodrugmentioning
confidence: 99%
“…All the patients having neurodegenerative disorder are treated with acetylcholinesterase inhibitor but recent studies have shown that butyl cholinesterase is also responsible for the disease, so MTDL drug class named Pleiotropic prodrug was designed which targets more than one pathway (Toublet et al, 2020) (Christophe & Patrick, 2018). These are butyl cholinesterase inhibitor as well as 5HT6 receptor antagonist and the prodrug is pleiotropic carbamate (Toublet et al, 2020). Another novel drug name Revastigmine, a pleiotropic prodrug that inhibits acetylcholinesterase as well as also targets 5HT receptor mainly 5HT4 receptor.…”
Section: Pleiotropic Prodrugmentioning
confidence: 99%